La formación y aprobación de la estrategia en las grandes empresas del ecuador: un estudio del caso - Guerrero Bejarano, Maria Auxiliadora (2017)
The decisions that are made for the companies affect their performance, for this reason it becomes important for academics and practitioners to understand how strategies are defined and approved in organizations.